A new genus and two new species of alvinocaridid shrimps (Crustacea: Decapoda: Caridea) from a hydrothermal vent field off northeastern Taiwan - Komai, Tomoyuki; Chan, Tin-Yam (Zootaxa, 2010)
Two new species of alvinocaridid shrimps are described from a hydrothermal vent field off northeastern Taiwan at depths of 252–300 m. Alvinocaris chelys n. sp. is morphologically very similar to A. williamsi Shank & Martin, 2003 from the Mid-Atlantic Ridge, and A. alexander Ahyong, 2009 from the southern Kermadec Ridge. These three species can be differentiated by the shape of the postrostral ridge, telson, the second segment of the antennular peduncle and the armature of the meri and ischia of the third pereopod. The second new species, although rather similar to Alvinocaris niwa Webber, 2004 from the Kermadec-Arc, is assigned to a new genus Alvinocaridinides gen. nov., which appears to be intermediate between Shinkaicaris Komai & Segonzac, 2005 and other derived genera including Opaepele Williams & Dobbs, 1995, Chorocaris Martin & Hessler, 1990 and Rimicaris Williams & Rona, 1986. Alvinocaridinides formosa n. sp. differs from Alvinocaris niwa by completely lacking any armature on the ischia of the third to fifth pereopods and by bearing two movable spines at the posterolateral angle of the uropodal exopod. These records constitute the first discovery of the family Alvinocarididae in Taiwanese waters and represent the shallowest occurrence for alvinocaridid shrimps.